Sirtuin family in lung adenocarcinoma - Cui Chen; Xiumin Liu; Zhe Xu; Juan Xu; Lei Gong; Xiaobo Wang (Discover Oncology)
Abstract Lung cancer is a highly aggressive malignancy that accounts for one of the greatest mortality rate in humans globally. Among various types of lung malignancies, lung adenocarcinoma (LUAD) stands out as the most common form. Sirtuins (SIRTs) are class III nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylases that comprise seven members (SIRT1-7). Sirtuins play a essentail role in various biological processes such as cellular differentiation, inflammation, apoptosis, metabolism, immune response, oxidative stress, mitochondrial homeostasis, and autophagy. Therefore, it is considered a potential therapeutic target for different kinds of pathologies including cancer, kidney diseases, and other conditions. While several reviews have been published on sirtuins and lung cancer, there remains a gap in the review regarding sirtuins specifically in LUAD. Herein, we not only elaborate on the roles of different sirtuins and their mechanisms in LUAD, but also discuss the potential application of sirtuins inhibitors and activators for LUAD therapy.